The Urgency of CISG Implementation in Indonesia - Nabilah Seviana (Jurnal Justiciabelen, 2025)
Sales contracts are the backbone of international trade in the world, regardless of their level of economic development. As a result, the CISG is regarded as a fundamental agreement of international trade law that should be widely ratified. The CISG has only been ratified by 95 nations, nevertheless. International private law will be used in the event that they have not ratified the CISG. The author is interested in offering a different perspective on the resolution of contract law violations under review from the perspective of the CISG because international private law has not fully protected interested parties due to the various regulations that apply to each country. As a result, the author is concerned that the CISG will be able to resolve the international contract violations under review. Research data kinds include primary legal materials, secondary legal materials, and tertiary legal materials. The research method uses normative legal research procedures with secondary data sources or data collected from library materials. This article was completed utilizing the appropriate legislative methodology relevant to the author’s topic of discussion. Because of the consistency of the agreements, approval of the CISG will unquestionably increase legal certainty in this transaction. Additionally, the CISG accepts the use of commercial customs and interparty customs to interpret the terms of the contract. Good faith is utilized as the guiding concept in the interpretation of the provisions and application of the contract, just as it is in Indonesian contract law.